PERBEDAAN KECEMASAN PADA PASIEN YANG AKAN MENJALANI OPERASI BESAR SEDANG DAN KECIL - Lermiana Br. Purba; Muchti Yuda Pratama; Ade Irma Khairani (Jurnal Riset Hesti Medan, 2017)
This study aims to look at the differences in anxiety in patients undergoing major surgery, medium, and small at the Hospital of Putri Hijau Medan. In line with the existing theory, to test the validity and reliability on the test the validity of measuring instruments, it turns out that valit 46 grain and based on the degree of reliability is equal to 0969. Measuring instrument used in this study had a high level of reliability (very reliable). To be able to analyze the data of this study tested the assumption that the distribution normality test and homogeneity test group. Based on the test normality distribution calculation kosmogorov-Smirnov shows research data analyzed has a distribution that is normally indicated by coefficient KS of 0.122 with P> 0.05 (P = 0089) three groups were used in this study is homogeneous with a coefficient of homogeneity of 2,724 with P > 0.05 (P = 0.077). Calculation of data analysis used in this research is the statistical analysis ANOVA one lane. Turns showed no differences were very signivikan anxiety among patients who will face major surgery, medium, and small, which is indicated by coefficient F = 17 385 with P <0:01 (P = 0:00). It turned out that patients undergoing major surgery  experience exyety at 103.73 100.07 Medium,skall amounting to 996.20Keywords: Difference anxious small medium and large operations